2016
DOI: 10.1186/s40880-016-0136-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of microRNA polymorphisms with the risk of head and neck squamous cell carcinoma in a Chinese population: a case–control study

Abstract: BackgroundMicroRNA (miRNA) polymorphisms may alter miRNA-related processes, and they likely contribute to cancer susceptibility. Various studies have investigated the associations between genetic variants in several key miRNAs and the risk of human cancers; however, few studies have focused on head and neck squamous cell carcinoma (HNSCC) risk. This study aimed to evaluate the associations between several key miRNA polymorphisms and HNSCC risk in a Chinese population.MethodsIn this study, we genotyped five com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Interestingly, we revealed that miR-605 rs2043556 A/G polymorphisms are significantly associated with UA and AMI. This potentially functional polymorphism within miR-605 has been reported to be associated with the risk of certain types of cancers in Chinese individuals [25][26][27]. We also demonstrated that the expression of mature miR-605 in cells transfected with the miR-605 rs2043556 G group is lower than that in cells transfected with rs2043556 A, which is consistent with studies of miR-605 in Li-Fraumeni syndrome [24].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, we revealed that miR-605 rs2043556 A/G polymorphisms are significantly associated with UA and AMI. This potentially functional polymorphism within miR-605 has been reported to be associated with the risk of certain types of cancers in Chinese individuals [25][26][27]. We also demonstrated that the expression of mature miR-605 in cells transfected with the miR-605 rs2043556 G group is lower than that in cells transfected with rs2043556 A, which is consistent with studies of miR-605 in Li-Fraumeni syndrome [24].…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have investigated the association between miR-605 rs2043556:T>C and cancer risk [ 82 ]. Specifically, the miR-605 C allele was associated with an increased risk of bladder cancer in a Caucasian population [ 60 ], and in gastrointestinal cancer, the C allele was significantly less common in the controls vs. cancer patients in an Asian population [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the miR-605 C allele was associated with an increased risk of bladder cancer in a Caucasian population [ 60 ], and in gastrointestinal cancer, the C allele was significantly less common in the controls vs. cancer patients in an Asian population [ 31 ]. However, rs2043556-C significantly decreased the oral squamous cell carcinoma risk in a Chinese population [ 82 ]. Only one article and one meta-analysis have evaluated the association between rs2043556 and BC risk.…”
Section: Discussionmentioning
confidence: 99%
“…A polymorphism of miRNA 605 gene was associated with increased risk of squamous cell carcinoma (Miao et al, 2016), Li-Fraumeni syndrome (Id Said and Malkin, 2015), prostate cancer (Huang et al, 2014), and gastrointestinal cancer (Zhang et al, 2012). MiRNA 605 was downregulated in melanoma cell lines and suppressed melanoma cell growth both in vitro and in vivo.…”
Section: Mirna 605mentioning
confidence: 99%